The implications of cold war on Malaysia state building process - Shuib, Md. Shukri; Keling, Mohamad Faisol; Ajis, Mohd Na'eim (Canadian Center of Science and Education, 2009)
The Cold War has affected the communities around the world. Malaysia was no exception in being affected by the turmoil the international world, particularly after the World War 2, due to ideological conflicts. Based on the domino theory, the ups and downs of particular country in terms of its, strong ideology, brings about network impacts to each country in the world. Thus, a freedom of Malaya and the establishment of Malaysia came from the history of Cold War which influenced the international scene. The establishment of Malaysia is seen as a mechanism to stop the influence of communism. The involvement leaders from Malaya, Singapore, Sabah and Sarawak as well as Brunei Darussalam in the agenda to ‘build’ Malaysia with the approval from democratic countries showed a very strong cooperation that communism was a threat. This contributed to the creation of a new and bigger country. The wise Malaysian leaders in negotiating and being united in facing the global threats at that time, has shown that Malaysia’s ‘project’ in stopping the communist theory which is also known domino theory, was successfully carried out and maintained till today. Therefore, Malaysia as a case study, on how a country was ‘built’ on the basis of stopping the spread of communism in saving the Southeast Asia from falling into the hands of communists, is unique and its effectiveness should be studied.